ANALISA KUALITAS PREPARAT TELUR CACING STH MENGGUNAKAN PEWARNAAN EOSIN 2% DAN PEWARNAAN ALTERNATIF LIMBAH GAMBIR - Bastian Darwin (IKesT Muhammadiyah Palembang, 2024)
Introduction: Worm infections are widespread in tropical and subtropical areas. Especially Indonesia, one of the countries that has quite high cases of worms, these cases are usually found in areas with high humidity, lack of personal hygiene, and poor environmental conditions. One of the laboratory tests that can be done to diagnose worm disease is a microscopic examination. Microscopic examination using stool samples requires staining which of course contains good dyes as support. This coloring substance is found in gambier waste (Uncaria gambier) in the form of catechin which is able to give a red and yellow color. Thus, gambier waste (Uncaria gambier) can be used as an alternative color to examine STH worm eggs. Research objective: to utilize catechins in gambier waste (Uncaria gambier) as a coloring agent to examine STH worm eggs. This research includes collecting feces samples, collecting gambier waste, processing gambier waste, making preparations using eosin staining and staining gambier waste, observing STH worm eggs microscopically. Research method: Laboratory experiment, carried out at the Parasitology Laboratory, Faculty of Science and Technology, Muhammadiyah Institute of Health Sciences and Technology, Palembang. The sample is feces. Research results: show that STH worm eggs can be stained with both stains, namely Gambier Waste Staining and Eosin Staining. Research conclusion: gambier waste coloring can be used as coloring for STH worm eggs. Staining gambier waste can be used as an alternative coloring to replace eosin dye for staining STH worm eggs